NAMAS ‘house’ and NAMAI ‘home’ in the Lithuanian Language and Culture - Rutkovska, Kristina (Lietuvių kalba, 2016)
The Lithuanian picture of house/home is deeply rooted in folk tradition – the ideal home is the rural home of a person’s childhood. In Lithuanian, there are two expressions that are used to designate the concept, the singular namas – which dictionaries tersely define as a building – and the plural namai, which stands for a broader space and a family staying together. The author discusses synonyms (and quasi-synonyms), antonyms (accenting the opposition between familiarity and strangeness), derivatives and collocations of these words. She reports the results of a questionnarie, which show that namas/namai is often mythicised as a paradise on earth, with the important motif of returning home. Proverbs keep guard over patriarchal relations in the family and portray home as a stronghold. Journalistic texts introduce the concept of a cosmopolitan home, open to the world. The features of the Lithuanian base picture of namas/namai are discussed according to the basic semantic aspects: social, psychosocial (sacralisation of home), mental, physical and functional (home as a shelter protecting individuals from the strange world they fear). Two profiles of the Lithuanian home are identified in the study: a romantic rustic profile grounded in the lasting relationship with the family, and a European, intelligentsia profile located wherever there are (any) people.
Keywords: house; concept; world view and language; cognitive linguistics